Synthesis of diverse α, ω-telechelic polystyrenes with di- and tri-functionality via tandem or one-pot strategies combining aminolysis of RAFT-polystyrene and a thiol–ene "click" reaction. Issue 55 (17th June 2015) - Zhang, Shuang-Shuang; Cui, Kun; Huang, Jin; Zhao, Qiao-Ling; Cao, Shao-Kui; Ma, Zhi
<x xml:space="preserve">Abstract</x> Diverse new α, ω-telechelic polystyrenes with di-/tri-functionality were synthesized via tandem/one-pot strategies combining aminolysis of RAFT-polystyrene and a thiol–ene "click" reaction.